Distantly reading race in the contemporary 'postrace' novel. Issue 1 (2nd January 2021) - Bose, Maria
ABSTRACT: Inspired by recent computationally assisted close readings undertaken by critics including Ryan Cordell, Paul Fleming, Michael Gavin, Matthew Jockers, Andrew Piper, Hoyt Long, Richard So, and Ted Underwood, this essay devises an account of Colson Whitehead's genre-bending zombie thriller Zone One (2011) based on visualisations of the text's lexical patterns, arguing that such an approach yields explanatory purchase on the relation between Zone One 's genre-fiction surface (i.e. its zombie plot and predominantly race-free lexicon) and what the majority of the novel's critics have intuited to be its literary-allegorical core (i.e. the novel's latent race-conscious ideological programme). Mobilising a low-tech, small-scale computational approach to Zone One 's distribution of explicit and implicit racial signifiers, I argue that attention to the novel's patterns of form and language reveals a racial grammar lurking beneath its chiefly unmarked lexicon. Through its careful distribution of racialising terms, Zone One, I suggest, embodies a 'viral' intertextuality keyed to processes of racial formation occurring beneath the discourse of 'postraciality' and within the hidden technical registers of the networked global economy.